2006
DOI: 10.1126/science.1123432
|View full text |Cite
|
Sign up to set email alerts
|

Cortical 5-HT 2A Receptor Signaling Modulates Anxiety-Like Behaviors in Mice

Abstract: Serotonin [5-hydroxytryptamine (5-HT)] neurotransmission in the central nervous system modulates depression and anxiety-related behaviors in humans and rodents, but the responsible downstream receptors remain poorly understood. We demonstrate that global disruption of 5-HT2A receptor (5HT2AR) signaling in mice reduces inhibition in conflict anxiety paradigms without affecting fear-conditioned and depression-related behaviors. Selective restoration of 5HT2AR signaling to the cortex normalized conflict anxiety b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
261
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(285 citation statements)
references
References 28 publications
21
261
3
Order By: Relevance
“…The pharmacological data are extended by the finding that gene knockout of the mouse Htr2a causes a decrease in anxiety-like behavior in various tasks (Weisstaub et al, 2006). Weisstaub et al were able to demonstrate that expressing 5-HT2A-Rs in the cortex of these knockout mice was sufficient to normalize the anxiety-like behavior, suggesting that cortical 5-HT2A-Rs normally serve to promote anxiety-like behavior.…”
Section: -Ht2a Receptorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pharmacological data are extended by the finding that gene knockout of the mouse Htr2a causes a decrease in anxiety-like behavior in various tasks (Weisstaub et al, 2006). Weisstaub et al were able to demonstrate that expressing 5-HT2A-Rs in the cortex of these knockout mice was sufficient to normalize the anxiety-like behavior, suggesting that cortical 5-HT2A-Rs normally serve to promote anxiety-like behavior.…”
Section: -Ht2a Receptorsmentioning
confidence: 98%
“…Precisely how this relates to the regulation of mPFC neuronal activity by 5-HT2A-Rs is not yet clear. Furthermore, although 5-HT2A-R knockout mice showed normal 'depression-related' behavior in the forced swim test, and a normal HPA-axis response to this stressor (Weisstaub et al, 2006) further examination of these mice for other stress-related behaviors would be informative. Such studies are encouraged by the increased PFC 5-HT2A-R binding found in depression (Meyer et al, 1999;Yatham et al, 2000), and the antidepressant efficacy of drugs with 5-HT2A-R antagonist properties (e.g., nefazodone, trazodone, mirtazapine) Millan, 2003).…”
Section: -Ht2a Receptorsmentioning
confidence: 99%
“…99 These mice show decreased anxiety-like behavior, and rescuing 5-HT 2A receptor expression in cortical neurons normalizes anxiety-like behavior. 99 It has also been suggested that stimulation of 5-HT 2A receptors in the dorsal periaqueductal gray matter induces panicolytic-like behavior in rats.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…The knockout mice exhibited greater exploratory and risk behavior in conflict paradigms, such as the open field, dark-light choice, elevated plus-maze, and novelty-suppressed feeding tests. In depression-related behaviors, as measured by the forced swim test and the tail suspension test, the mice did not differ significantly from wild-type mice (54).…”
Section: Fig 3 Group Mean Ventilatory Response To Itto For Experimementioning
confidence: 71%
“…Activation of HTR2A receptors weakens the sensory gating so that more sensory information is able to reach consciousness, which in turn can lead to the pathology of anxiety disorders (29). Behavioral studies in HTR2A knockout mice have shown changes in anxiety-related but not depression-related paradigms (54). The knockout mice exhibited greater exploratory and risk behavior in conflict paradigms, such as the open field, dark-light choice, elevated plus-maze, and novelty-suppressed feeding tests.…”
Section: Fig 3 Group Mean Ventilatory Response To Itto For Experimementioning
confidence: 99%